COMBINATION THERAPY OF HYPERTENSION - A RELIABLE WAY TO TARGET ACHIEVE - Yu. V. Lukina; S. Yu. Martsevich (Столичная издательская компания, 2016)
Data of evidence-based cardiology and clinical guidelines that define the position of combined therapy to achieve the targets of hypertension (HT) treatment (achievement and maintenance of the target blood pressure (BP) level, protection of the target organs, improvement of the quality of life in hypertensive patients) are presented in the article. The advantages of rational combined therapies (potentiation of antihypertensive effect, reduction of a number of adverse events) are considered. Studies of therapeutic efficacy and safety of combined antihypertensive therapy based on generics are important. The advantages of combined therapy in achievement of target BP levels are presented on example of comparative study of new generic and original amlodipine in patients with HT of 1-2 degrees. Target BP level was reached respectively in 90% and 97% of patients with HT in groups of generic and original amlodipine combined with generic lisinopril and hydrochlorothiazide. Safety profile was acceptable. This confirms the high efficacy of amlodipine + lisinopril + hydrochlorothiazide combination, including one on the basis of generics.